ABOUT PHASE INTERDEPENDENCE AND POSSIBILITY OF WALSH FUNCTIONS SYSTEM REDUCTION - Petryshyn, Lubomyr (International Journal of Computing, 2014)
The system of Walsh functions is the multiplicative group of Rademacher- and Gray-function systems. The system contains discrete-harmonic sin-components of Rademacher functions, cos-components of Gray functions, and also discrete-nonharmonic components of Walsh functions. Pair phase interdependence of complete Walsh system functions is established. Subsystems of odd (sin-components) and even (cos-components) of Walsh functions as bases of theoretic-number transformations are constructed. The perspective of the future researches of transformations efficiency for digital signal processing in the proposed function systems is defined.